Improving the Methodological Framework for Statistical Accounting of Environmental Protection Expenditure in the Context of Renewable Energy Sources - Т. KOBYLYNSKA; O. MOTUZKA; N. PARFENTSEVA (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2019)
The article is devoted to improvements of the methodological framework for statistical accounting of environmental protection expenditure in Ukraine in the context of renewable energy sources (wind and solar energy). It is argued that any study focused on accounting of environmental protection expenditure or development of renewable energy sources needs computations and analyses of indicators based on statistical data. Problems of improvements in statistical accounting are, therefore, have critical significance for such studies. The important objective is related with improvements of statistical accounting of the capacities generating energy from alternative sources and costs on their installation and modernization, which will enable to compare data all the levels, reveal main tendencies, patterns and changes, assess indicators and take sound decisions on environmental protection.  The article contains an analysis of statistical indicators on alternative energy sources and their recording in the satellite account of environmental protection expenditure. The sources of data for reporting wind and solar energy indicators in the satellite account of environmental protection expenditure in Ukraine are shown.   The satellite account of environmental protection expenditure is constructed using information from various sources. The study demonstrates that the official statistical observation by form 1-Environmental expenditure (annual) “Environmental protection expenditures and environmental payments” can be used as the main source for indicators of capital and current environmental protection expenditure in Ukraine.Therefore, the sources of administrative information, i. e. data collected for other purposes and characterizing selected aspects of environmental protection expenditure, should be used to improve the existing methodological framework.